AB0020 Comparison of synovial mmp-1 and timp-1 levels in patients with various inflammatory arthritides. (1st June 2001) - Pay, S; Erdem, H; Serdar, M; Dinc, A; Simsek, I; Turan, M
Abstract : Background: Some inflammatory arthritides like a rheumatoid arthritis cause erosion in bones and destruction in cartilage, but others such as Behçet's Disease (BD) and Familial Mediterranean Fever (FMF) do not. Objectives: The purpose of this study was to investigate synovial levels of matrix metalloproteinase ?1 (MMP-1) known to break collagen, and tissue inhibitor of metalloproteinase (TIMP-1), its natural antagonist, in patients with various inflammatory disorders. Methods: One hundred and nine patients with different inflammatory arthritides were enrolled in the study (20 BD, 20 FMF, 24 spondyloarthropathy (SPA), 26 rheumatoid arthritis (RA) and 19 osteoarthritis (OA)). All patients had at least one-sided knee arthritis from which synovial fluid samples were obtained. Patients with BD, FMF and SPA constituted three study groups. Patients with RA and OA were used as control groups. Synovial MMP-1 and TIMP-1 levels were measured by two-step sandwich ELISA. Results: The mean levels of synovial MMP-1 and TIMP-1 of the study and control groups presented in Table 1 . Conclusion: Although FMF and BD are generally characterised by nonerosive arthritis, our results showed that synovial MMP-1 levels of patients with BD and FMF were not different from the patients with RA, which is a well-known erosive arthritis. We suggested two possible explanations for these unexpected data. First, BD and FMF generally cause short term arthritic attacks, remitting without permanent damage. Second, high synovial MMP-1 levels in BD and FMF may be resulted from extra articular origin, because of their systemic nature. The comparison of synovial MMP-1 levels between RA and SPA was statistically significant. This may help to explain why SPA causes less prominent destruction in cartilages and erosion in bones than RA. Except OA, the difference between the groups with respect to the synovial TIMP-1 levels was statistically insignificant.